Up-Regulation of RIP3 Alleviates Prostate Cancer Progression by Activation of RIP3/MLKL Signaling Pathway and Induction of Necroptosis - Wang, Ke-jie; Wang, Kai-yun; Zhang, Hui-zhi; Meng, Xiang-yu; Chen, Jun-feng; Wang, Ping; Jiang, Jun-hui; Ma, Qi (Frontiers in Oncology, 2020)
Background：The receptor-interacting protein kinase 3 (RIP3/RIPK3) was recently found to be a critical regulator of programmed necrosis/necroptosis. However, the biological role and clinical significance of RIP3 in prostate cancer remain obscure. Methods: Western blotting and QRT-PCR were performed to detect the level of RIP3 in prostate cancer cells. Fixed cancer tissue and normal tissue specimens were subjected to immunohistochemical analysis of RIP3. Cell migration and invasion abilities were evaluated by transwell assays. In vitro proliferative ability was examed by MTS. And in vivo nude mice model were used to evaluate the effect of RIP3 ectopic expression on proliferative capability. Cell cycle of prostate cancer cells were analyzed by flow cytometry. Changes in some related proteins caused by RIP3 overexpression were explored using Western blotting. Results: RIP3 was significantly down-regulated in prostate cancer cell lines and clinical prostate tumor samples. And over-expressing RIP3 suppressed the migration and invasion of prostate cancer cells. Two important matrix metalloproteinases MMP2, MMP9 which enables the destruction of the histological barrier of tumor cell invasion and three mesenchymal markers Vimentin, fibronectin, and N-cadherin were under-expressed due to the overexpression of RIP3, but the E-cadherin level which is the epithelial marker was increased. Furthermore, our results also showed that RIP3 can inhibit the proliferation and tumorigenicity of prostate cancer cells both in vitro and in vivo by phosphorylating MLKL, which were reversed by MLKL inhibitor treatment, indicating that necroptosis was involved in cell death. Conclusions: Taken together, these findings indicated that RIP3 is responsible for the progression of prostate cancer, suggesting that RIP3 might have the potential to be a prognostic marker or a therapeutic target against prostate cancer.